2014
DOI: 10.7314/apjcp.2014.15.21.9391
|View full text |Cite
|
Sign up to set email alerts
|

Internal-External Percutaneous Transhepatic Biliary Drainage for Patients with Malignant Obstructive Jaundice

Abstract: Asian Pac J Cancer Prev, 15 (21), 9391-9394 IntroductionPercutaneous transhepatic biliary drainage is becoming more and more useful as a palliative treatment for patients with malignant obstructive jaundice, which could not only significantly reduce bilirubin levels, improve liver function and prolong survival time, but also be used as a preoperative drainage, provide the conditions for subsequent treatment (Boursier et al., 2009;Herzog et al., 2012;Kaya et al., 2012;Zhu et al., 2012). In our center, if the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Furthermore, infection was found to be more frequent as the cause of death in the Catheter group. This may be resulted from ex vitro infection tracking along the drainage catheter [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, infection was found to be more frequent as the cause of death in the Catheter group. This may be resulted from ex vitro infection tracking along the drainage catheter [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies also have reported cholangitis as the main complication.Teixeira et al, in their study of 71 patients with MBO reported cholangitis in 66.2% of cases 10. Xu et al, reported incidence of new biliary infection after internal-external biliary drainage reached 47.6% in their study of 42 patients with MBO 12. Sut et al., in their study of 21 patients with MBO had had cholangitis in 19% patients after PTBD.…”
mentioning
confidence: 95%
“…1 Percutaneous transhepatic biliary drainage catheters have been widely used in clinical practice to relieve malignant obstructive jaundice. 2 Only a few case reports of tumor seeding from percutaneous biliary drainage catheter placement have been reported in the literature, [3][4][5][6][7][8] raising the possibility that tract seeding may be an underdiagnosed complication of percutaneous biliary drainage catheter placement. As FDG PET/CT is routinely used in clinical surveillance during a cancer patient's treatment process, it is of high importance to have a complete history of the patient's previous interventional procedures.…”
mentioning
confidence: 99%